Dataset "Radar geometries used during the PhD of Alexander Hagelberg" - Hagelberg, Alexander; Andre, Daniel (Cranfield University, 2024)
This excel file contains the co-ordinates used in the experiments of the PhD of Alexander Hagelberg. These trajectories were used in various papers which are listed in the headers.
Keywords: Synthetic Aperture Radar; Radar imaging; Geometries